การเพิ่มประสิทธิภาพในการเป็นสำนักงานดิจิทัลของ สำนักงานคณะกรรมการกิจการกระจายเสียง กิจการโทรทัศน์ และกิจการโทรคมนาคมแห่งชาติ - ฐิณัชญสินี รวิชญทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research aims to study factors that affect the enhancement of efficiency improvement of the Office of the National Broadcasting and Telecommunications Commission or the Office of the NBTC as a digital organization and to improve its ranking from number 6 for the Digital Government Awards 2020 of Digital Government Development Agency. It also aims to study guidelines and suggestions in improving the development of the Office of the National Broadcasting and Telecommunications Commission into a digital organization. This qualitative paper collects data from in-depth interviews using semi-structured questions with various relevant stakeholders who use the services of the Office of the National Broadcasting and Telecommunications Commission and analyzes the data using content analysis together with descriptive data analysis methods.The results reveal that the factor impacting the efficiency improvement of the Office of the National Broadcasting and Telecommunications Commission as a Digital Organization is the information integration of officers due to the lack of communication between officers nowadays. For instance, a task that creates both a system for providing services to customer and a system for internal operation results in both overlapping systems and separate systems in the organization. In addition, rules and guidelines from external audit bodies are other factors that discourage the organization from becoming a digital organization. In terms of other factors, the Office of the National Broadcasting and Telecommunications Commission strives and is prepared to support the organization improvement as a digital organization, such as the factor of policy and the factor of upskilling personnel with digital competence. Moreover, the Office of the NBTC also supports the budget allocation for digital technology system projects in order to reduce the number of systems to a single window for both internal and customer service systems.Nevertheless, being an efficient digital organization requires more support from top-level management and the government of Thailand. This includes enacting laws and regulations on disbursement to ensure they align with audit agencies and also includes other types of support that are inclusive and encourage the organization into becoming more of a digital organization in order to promote the government of Thailand as a successful digital government.